Delayed urticaria or anaphylaxis after consumption of red meat with evidence of alpha-gal sensitisation. Issue 12 (28th December 2020) - Garcia, Maria Beatriz; Gomez-Samper, Andres F; Garcia, Elizabeth; Peñaranda, Augusto
Abstract : Food allergies to red meat, specifically to galactose-alpha-1, 3-galactose (alpha-gal), a mammalian oligosaccharide, are considered to be very rare, especially in Asia and Latin America. Most of the cases reported are characterised by symptoms of delayed urticaria or anaphylaxis after the consumption of red meat. Sensitisation to red meat has been linked to the use of cetuximab or tick bites, especially from the Amblyomma americanum and Ixodes spp species. Here, we documented a case study from a Colombian male patient with symptoms of delayed urticaria and anaphylaxis with a history of tick bites in Colombia. The patient presented with IgE antibodies specific to alpha-gal, which is the most common epitope linked to red meat allergy induced by tick bites.